INTERNET DAN PEWARTAAN DALAM PESAN PAUS UNTUK HARI KOMUNIKASI SEDUNIA 2002-2016 - Matheus Purwatma (Jurnal Orientasi Baru, 2016)
The Message of the Holy Father John Paul II for 36th the World Communication Day 2002, reflects on the means of the Internet for evangelization, "Internet: A New Forum for Proclaiming the Gospel". The Internet is a new forum into which the Holy Father encourages the Christians to follow the Lord's command to "put out into the deep: Duc in altum! (Lk 5:4). The subsequent Messages for the World Communication Day give some directions to the Christians on the internet as a new social communication media. Internet is modern Aeropagus, which is unifying humanity and connecting each other in the same time, and has its own languages and cultures. It is a challenge for evangelization. The Holy Fathers not only invites to use internet as means of proclaiming the Gospel, but integrates the message of the Gospel in it.